Regulating crime prevention design into consumer products: learning the lessons from electronic vehicle immobilisation - Rick Brown
Foreword Despite significant reductions in recent years, acquisitive property crime remains the single largest crime category, with over 700,000 offences recorded annually by police in Australia. There is potential to further reduce the scale of such offending and the subsequent costs to society by focusing attention on the design of frequently stolen consumer products in order to reduce their vulnerability to theft. While there is a variety of ways of engaging with manufacturers, government regulation may ultimately be required if other approaches prove unsuccessful. This paper examines the lessons that can be learned as a result of the regulation of motor manufacturers to install electronic immobilisers on all new cars from July 2001, which has contributed to significant reductions in vehicle crime over the past decade. Eight generic lessons for future regulation of crime prevention design in consumer products are outlined. These lessons should assist policymakers to identify how the costs incurred by the criminal justice system in dealing with acquisitive property crime could be shifted to manufacturers, who arguably contribute to the problem by the way they design and market their consumer products